2009
DOI: 10.1016/j.jvs.2009.06.010
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of 10 hemostatic dressings in a groin puncture model in swine

Abstract: The findings indicated that the efficacy of Woundstat, Celox, X-Sponge, and ACS+ were similar and superior in improving survival, hemostasis, and maintenance of mean arterial pressure in an actively bleeding wound caused in this severe vascular injury model.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
55
0
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 71 publications
(59 citation statements)
references
References 23 publications
3
55
0
1
Order By: Relevance
“…Two injury models [6][7][8][9][10][11][12][13], a full femoral transection (including artery and vein) and a femoral artery puncture yield massive blood loss in the early phase of bleeding and severe hemorrhagic shock consequences if untreated. Our previous results indicated that dressing efficacy outcomes were different across these two injury models [1,2]. There was more post-treatment bleeding after the compensatory phase in the puncture injury model than the transection.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Two injury models [6][7][8][9][10][11][12][13], a full femoral transection (including artery and vein) and a femoral artery puncture yield massive blood loss in the early phase of bleeding and severe hemorrhagic shock consequences if untreated. Our previous results indicated that dressing efficacy outcomes were different across these two injury models [1,2]. There was more post-treatment bleeding after the compensatory phase in the puncture injury model than the transection.…”
Section: Introductionmentioning
confidence: 99%
“…In an effort for better hemostatic control in noncompressible areas such as the neck or the groin where tourniquets cannot be used, a variety of highly effective hemostatic dressings have become available and can be selected according to various qualities like their physical nature. In a previous series of experiments comparing 10 hemostatic dressing products to compressed gauze (as the standard of care) [1,2], three products, X-Sponge (Z-Medica, Wallingford, CT), a synthetic gauze coated with kaolin; Woundstat (TraumaCure, Bethesda, MD), a smectite/polymer granular product; and Celox (Sam Medical Products, Newport, OR), a chitosan-based product, were found to be the most effective dressings for survival, blood loss, and bleeding control among those tested. A key observation in those experiments was that the fabric-based products (e.g., X-Sponge) were similar in form to standard gauze and could be relatively easily removed, leaving a clean wound, ready for surgical repair.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The form of a hemostatic agent impacts the removability of dressing residues from the wound as well as the potentially harmful effects (Arnaud et al 2009, Clay et al 2010, Kheirabadi et al 2010. Herein, we did not observe any differences in the macroscopic or microscopic changes in the internal organs among the groups examined.…”
Section: Discussionmentioning
confidence: 48%
“…The newest agents, which consist of gauze dressings impregnated with kaolin and chitosan, are more effective and simple to use, and have a low risk of tissue injury and thromboemboli formation (Kheirabadi et al 2010, Johnson et al 2014. The majority of studies on the effectiveness of hemostatic agents using animal models have examined the influence of a short-term dressing application that was no longer than a few hours (Arnaud et al 2009, Kheirabadi et al 2010, Littlejohn et al 2011, Gegel et al 2012). There are no previously published studies on the consequences of the long-term application of hemostatic dressing, which is occasionally necessary on the battlefield, especially when the individual must be transported hundreds of kilometers to a medical facility.…”
Section: Discussionmentioning
confidence: 99%